2015
DOI: 10.1080/ac.70.1.3064594
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical exercise on arterial stiffness parameters in young sportsmen

Abstract: We applied a feasible, clinically useful method which allowed us to measure changes in aortic PWV and Alx during acute, single-bout exercise on the basketball court in young sportsmen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Again in one of the very few studies with basketball players in literature Ratgeber et al did not find any difference in central pwv between 11 and 16 years young basketball players (5.82 m / sec) and age adjusted sedentary controls (5.83 m / sec). 25 The authors discussed that the young aortic wall was very elastic and increased blood pressure would not cause any stiffness of the aortic wall. Similarly, in our study basketball players who exercised regularly 15 hours in average per week for one year had lower central arterial stiffness values compared to sedentary controls.…”
Section: Resultsmentioning
confidence: 99%
“…Again in one of the very few studies with basketball players in literature Ratgeber et al did not find any difference in central pwv between 11 and 16 years young basketball players (5.82 m / sec) and age adjusted sedentary controls (5.83 m / sec). 25 The authors discussed that the young aortic wall was very elastic and increased blood pressure would not cause any stiffness of the aortic wall. Similarly, in our study basketball players who exercised regularly 15 hours in average per week for one year had lower central arterial stiffness values compared to sedentary controls.…”
Section: Resultsmentioning
confidence: 99%
“…After dynamic exercise, a significant increase in aortic PWV was seen in the oldest group (15-16 years). The authors also reported a decrease in Aix in the same age group, which did not reach statistical significance (Rátgéber et al, 2017).…”
Section: Effects Of Various Types Of Physical Training On Arterial Stiffnessmentioning
confidence: 86%
“…Some other studies reported no differences in aortic PWV between endurance athletes and healthy non-athlete controls (Dulai et al, 2011;Rátgéber et al, 2017). The effects of intense resistance training on arterial compliance were also evaluated, but the results were contradictory (Miyachi, 2013).…”
Section: Effects Of Various Types Of Physical Training On Arterial Stiffnessmentioning
confidence: 99%
“…There is little consensus regarding the influence of exercise on arterial stiffness in youth. Ratgeber et al ( 2015 ) similarly found no influence in a cross-sectional comparison of trained and untrained children, others have reported significantly lower arterial stiffness following HIIT (Chuensiri et al 2018 ), circuit training (Watts et al 2004 ), aerobic training (Meyer et al 2006 ) or a combined aerobic and resistance training protocol (Farpour-Lambert et al 2009 ). The variation in the training protocols and the use of flow-mediated dilation or PWV to assess arterial stiffness limit conclusions regarding the basis for these equivocal findings.…”
Section: Discussionmentioning
confidence: 98%